Pancreatic Damage and Radiological Changes in Patients With COVID-19 - Bozdag, Ahmet; Eroglu, Yesim; Tartar, Ayse Sagmak; Bozdag, Pinar Gundogan; Aglamis, Serpil (Springernature, 2021)
Background and objective The novel coronavirus disease 2019 (COVID-19) primarily affects the lungs. However, others organs are also affected in varying degrees. We aimed to investigate the changes in pancreatic density on CT and its correlation with amylase/lipase values in patients diagnosed with COVID-19. Materials and methods Radiological changes using non-contrast CT and amylase/lipase values were evaluated retrospectively in patients admitted to the pandemic clinic. The patients were classified into two groups: [polymerase chain reaction (PCR)-positive and PCR-negative]. The correlation and difference between the data were evaluated statistically. Results There was no significant difference with respect to age and gender between the two groups (PCR-positive and PCR-negative). There was a significant difference in the head, neck, trunk, and tail of the pancreas and mean density values, but no statistically significant difference in amylase and lipase values between the two groups. No significant correlation was found using Spearman's correlation test. Conclusion Based on our findings, pancreatic involvement and severe necrotizing pancreatitis can be seen in COVID-19 patients. Pancreatic involvement is more common in patients with severe disease. Patients with gastrointestinal complaints should be evaluated for pancreatitis and their amylase/lipase values should be assessed. We believe that decreased pancreatic density on CT scans can be an early sign of pancreatitis.
Keywords: pancreas; pancreatitis; covid-19; tomography; pancreatic injury